The Four Ceremonial Occasions in Korean Traditional Culture: Past and Present - Iliyaskyzy, Д.; Abagan, А.Б.; Saudanbekova, Ш.Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The rapid process of globalization creates many challenges to national and state interests. The main objective of this article is to analyze the preservation of the traditional life cycle rite in the daily life of Koreans, dating back to the Joseon dynasty, in the modern conditions of the rapidly developing and changing society of South Korea, to determine the attitude of modern Korean society, to study the laws adopted by the government regarding rituals. The author's hypothesis is that the Korean people are trying to combine new and traditional elements of the rituals of the «Four Ceremonial Occasions» without losing the deep cultural meaning, forms and value, but adding a modern interpretation that is understandable and attractive to younger generations. Relevance and novelty: the experience of the Korean people, rationally combining traditional culture and the process of globalization is consideredand for the first time the internal and external factors that led to the transformation of customs in South Korea were studied. Research methods: this work uses historical and anthropological analysis, general theoretical methods (analysis, synthesis and abstraction), analysis of sources. The result of the study: the Korean people not only preserved their national values, traditional culture and rituals, but also rationally synthesized the ancient core and the new shell, ultimately receiving a transformed cultural ritual. It was established that the conduct of traditional rituals is controlled by the state.